Effective Manipulation of Spin Dynamics by Polarization Electric Field in InGaN/GaN Quantum Wells at Room Temperature. Issue 13 (1st June 2020) - Liu, Xingchen; Tang, Ning; Zhang, Shixiong; Zhang, Xiaoyue; Guan, Hongming; Zhang, Yunfan; Qian, Xuan; Ji, Yang; Ge, Weikun; Shen, Bo
Abstract: III‐nitride wide bandgap semiconductors are favorable materials for developing room temperature spintronic devices. The effective manipulation of spin dynamics is a critical request to realize spin field‐effect transistor (FET). In this work, the dependence of the spin relaxation time on external strain‐induced polarization electric field is investigated in InGaN/GaN multiple quantum wells (MQWs) by time‐resolved Kerr rotation spectroscopy. Owing to the almost canceled two different spin–orbit coupling (SOC), the spin relaxation time as long as 311 ps in the MQWs is obtained at room temperature, being much longer than that in bulk GaN. Furthermore, upon applying an external uniaxial strain, the spin relaxation time decreases sensitively, which originates from the breaking of the SU (2) symmetry. The extracted ratio of the SOC coefficients shows a linear dependence on the external strain, confirming the essential role of the polarization electric field. This effective manipulation of the spin relaxation time sheds light on GaN‐based nonballistic spin FET working at room temperature. Abstract : GaN‐based wide bandgap semiconductors hold great potential in developing spintronic devices working at room temperature. The effective manipulation of the spin dynamics by strain‐induced polarization electric field is confirmed in InGaN/GaN quantum wells (QWs) using time resolved Kerr‐rotation spectroscopy. Such an effective manipulation paves a new approach toward using wurtzite nitride semiconductor multiple QWs structures in developing a nonballistic spin field‐effect transistor.